Question
Solve the quadratic formula to solve \( -8 x^{2}+10 x+3=0 \) • \( x=\square \) Simplify your answers, using square roots as needed. If there is more than 1 solution, separate the answers with a comma. Question Help: \( \square \) Video Submit Question
Ask by Garza Kelly. in the United States
Feb 03,2025
Real Tutor Solution
Tutor-Verified Answer
Answer
\( x = \frac{3}{2},\ -\frac{1}{4} \)
Solution
To solve the quadratic equation \( -8x^{2} + 10x + 3 = 0 \) using the quadratic formula, follow these steps:
### Quadratic Formula:
The quadratic formula is given by:
\[
x = \frac{ -b \pm \sqrt{b^{2} - 4ac} }{2a}
\]
where \( a \), \( b \), and \( c \) are coefficients from the quadratic equation \( ax^{2} + bx + c = 0 \).
### Identify the Coefficients:
For the equation \( -8x^{2} + 10x + 3 = 0 \):
- \( a = -8 \)
- \( b = 10 \)
- \( c = 3 \)
### Calculate the Discriminant:
\[
\Delta = b^{2} - 4ac = (10)^{2} - 4(-8)(3) = 100 + 96 = 196
\]
\[
\sqrt{\Delta} = \sqrt{196} = 14
\]
### Apply the Quadratic Formula:
\[
x = \frac{ -10 \pm 14 }{2(-8)} = \frac{ -10 \pm 14 }{ -16 }
\]
### Find Both Solutions:
1. **Using the plus sign (+):**
\[
x = \frac{ -10 + 14 }{ -16 } = \frac{4}{-16} = -\frac{1}{4}
\]
2. **Using the minus sign (−):**
\[
x = \frac{ -10 - 14 }{ -16 } = \frac{ -24 }{ -16 } = \frac{24}{16} = \frac{3}{2}
\]
### Final Solutions:
\[
x = \frac{3}{2},\ -\frac{1}{4}
\]
**Answer:** \( x = \frac{3}{2},\ -\frac{1}{4} \)
Reviewed and approved by the UpStudy tutoring team
Like
error msg
Explain
Simplify this solution
Beyond the Answer
To solve the quadratic equation \(-8x^2 + 10x + 3 = 0\), we can use the quadratic formula: \[ x = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} \] Here, \(a = -8\), \(b = 10\), and \(c = 3\). 1. First, we calculate the discriminant: \[ b^2 - 4ac = 10^2 - 4(-8)(3) = 100 + 96 = 196 \] 2. Now apply the quadratic formula: \[ x = \frac{-10 \pm \sqrt{196}}{2(-8)} = \frac{-10 \pm 14}{-16} \] 3. This gives us two possible solutions: \[ x_1 = \frac{4}{-16} = -\frac{1}{4}, \quad x_2 = \frac{-24}{-16} = \frac{3}{2} \] Therefore, the solutions are \( x = -\frac{1}{4}, \frac{3}{2} \).